PENINGKATAN KOMPETENSI PENGETAHUAN BUKU BESAR AKUNTANSI PERUSAHAAN DAGANG PADA SISWA SMA TARSISIUS 1 - Widyasari; Ivonne Patricia (Jurnal Serina Abdimas, 2024)
Proficiency in accounting plays a pivotal role in understanding economic transactions and managing businesses. In the midst of daily life, accounting knowledge is crucial for identifying, recording, and communicating financial transactions. However, the high school curriculum in Indonesia often treats accounting merely as a sub-subject under the umbrella of economics, resulting in a low level of interest among students. This is particularly due to the perception that accounting is closely associated with numbers. To address this challenge, a community service activity was conducted at Tarsisius 1 High School, focusing on a deeper exploration of the concepts related to the ledger in accounting for trading companies. This initiative aims to provide a more profound understanding of ledger concepts, a key aspect of accounting systems. Tarsisius 1 High School collaborated as a partner, offering full support for discussing and elucidating ledger concepts in more detail. On November 15, 2023, this activity was conducted in a face-to-face (offline) format. Participants gained a profound understanding of the concepts of perpetual and periodic ledger methods, along with quiz questions designed to hone their accounting skills. The goal is not only to improve students' comprehension of the accounting ledger for trading companies but also to stimulate their interest in pursuing accounting as a major in higher education, particularly at Tarsisius University as a potential program of study. The enhancement of ledger knowledge is expected to equip students with a solid foundation in accounting, instilling confidence in them to explore and pursue careers in this field in the future.